Age polyethism drives community structure of the bacterial gut microbiota in the fungus‐cultivating termite Odontotermes formosanus. (14th October 2015) - Li, Hongjie; Dietrich, Carsten; Zhu, Na; Mikaelyan, Aram; Ma, Bin; Pi, Ruoxi; Liu, Yu; Yang, Mengyi; Brune, Andreas; Mo, Jianchu
Summary: Fungus‐cultivating termites (Macrotermitinae) possess an elaborate strategy of lignocellulose digestion. It involves a lignocellulose‐degrading fungal symbiont (genus T ermitomyces ), a diverse gut microbiota and a characteristic labour division in food processing. In this study, using pyrotag sequencing and electron microscopy, we analysed the bacterial microbiota in the hindgut of O dontotermes formosanus and its fungus comb to investigate the spatial organization, establishment and temporal succession of the bacterial communities colonizing specific microhabitats. Our results document strong differences between the communities at the hindgut epithelium and the luminal fluid of newly moulted, young and old worker termites. The differences in community structure were consistent with the density, morphology and spatial distribution of bacterial cells and the pools of microbial metabolites in the hindgut compartment, underlining that both gut development and the age‐specific changes in diet affect the composition and functional role of their gut microbiota. These findings provide strong support for the concept that changes in diet and gut environment are important determinants of community structure because they create new niches for microbial symbionts.